John Constantine, Hellblazer. India - Milligan, Peter (DC Comics, 2010)
"Constantine leaves the UK and heads to India on a quest for purity in an effort to resurrect his dead girlfriend. But something wicked haunts the slums of Mumbai, leaving beautiful young women in its wake. An incredible clash of old and new cultures sets the stage for Constantine in India as he mingles with street kids, billionaires and Bollywood. But can he pay the price for enlightenment without losing his sanity? With greed, sex, demons and dancing, Mumbai has never been hotter than this."--Amazon.com.